Multicentre Spectrum of Esophageal Motility Disorders in the Indian Subcontinent - Jain, Mayank; Baijal, Rajiv; Jayanthi Venkataraman, Melpakkam Srinivas, Piyush Bawane (International Journal of Innovative Research in Medical Science, 2017)
Background - Motor disorders of the esophagus are rare and regional variations in their occurrence have not been studied in India. Aim and objectives - To study the spectrum of major and minor motor disorders in patients with motor dysphagia at three centres across India. Materials and Methods - This prospective data collection was done over a period of one year at three centres in India. Demographic details, symptoms at presentation and manometric diagnosis were recorded. The data was analysed using appropriate statistical tests. Results - Motor dysphagia is commoner in males and median age of presentation is the fifth decade. Dysphagia and regurgitation are the commonest symptoms. Achalsia is the commonest disorder, though the predominant subtype varies from centre to centre. Ineffective motility is the second commonest cause across all centres. Distal esophageal spasm and hypertensive peristalsis were only reported from Central India